MONITORING HEALTH SERVICE SATISFACTION IN HOSPITAL VIA SMARTPHONE IN CENTRAL SULAWESI - Zainul Zainul; Nasrul Nasrul; Fahmi Hafid (Jurnal Kesehatan Prima, 2018)
Abstract: The purpose of this study was to create monitoring model of a satisfaction of hospital health servicesbased on Smartphone in Central Sulawesi. The research design was Cross-sectional. The sample was 384 respondents through accidental sampling that were implemented at RSU Anutapura Palu, RSU Anutaloko Parigi and RSUD Luwuk. Data was collected by electronic forms in smartphone through google apps, analyzed with SPSS version 17.0. The results showed respondents at Anutapura Palu hospital 44.8%, Anutaloko Parigi 35.4% and Luwuk 19.8%. Male 60.2%. Bachelor (S1) 53.9%, State civil apparatus 51.8%. BPJS Insurance 53.5%. Respondents selected a hospital because of the location easy to reach (54.9%) Visit of Polyclinic (50%) to control health (44.3%). Respondents expressed satisfaction with hospital service in Central Sulawesi (78,6%) based on requirement, service time, Product Specification, Executor's competence, Service report, Complaints Handling, Suggestion and Input respectively were 72,9%, 69,3% , 68.7%, 70.3%, 73.2%, 75.5, 69.5% and 71.7% respectively. Model monitoring by using google apps (Documents, Sheets and Bit.ly). This research suggests that hospitals can use google apps via smartphones to measure patient satisfaction with hospital services. Monitoring hospital service satisfaction and responding promptly to complaints can increase public confidence in hospital services.Keywords: Service monitoring, hospital, smartphone.